Quasi-Sentence Constructions (Shibh al-Jumlah) in Surah al-Qadr: A Syntactic-Semantic Analysis of Transcendental Space and Time - Milah, Aang Saeful; Syofi, Raihan; Mubarok, Muhamad Nizar; Agresa, Agresa; Setiawan, Rizky (Published by Center for Research and Community Service (LP2M) in cooperation with the Postgraduate Program of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2026)
This study examines how quasi-sentence constructions (shibh al-jumlah) contribute to temporal and spatial meaning in Surah al-Qadr. It employed a qualitative textual design combining Qur’anic stylistics, formal Arabic syntax, and contextual semantics. The corpus comprised the complete Arabic text of Q.S. al-Qadr [97]:1–5. The analysis identified each quasi-sentence, classified its structure, examined its taʿalluq (syntactic attachment), and interpreted its function within the immediate context. Six constructions were identified: fī laylati al-qadr, min alfi shahr, fīhā, bi-idhni rabbihim, min kulli amr, and ḥattā maṭlaʿi al-fajr. All six take the form of al-jār wa al-majrūr (prepositional phrases); no independent al-ẓarf (adverbial) construction was found. Their governors and functions vary, expressing temporal location, comparison, contextual reference, divine permission, source or scope, and a temporal endpoint. Temporal organization is more directly encoded than spatial location, while spatial meaning is inferred from the clause describing the angels’ descent rather than from fīhā alone. The study provides a focused syntactic-semantic account of Surah al-Qadr without extending its findings into a comprehensive theory of Qur’anic cosmology.